The Phillips Curve in the United States and Canada: A GARCHDCC Analysis - Yang, Lu; Hamori, Shigeyuki (Journal of Reviews on Global Economics, 2014)
By applying the GARCH-DCC model, we reexamine the Phillips curve based on a time-varying correlation analysis for Canada and the United States from January 1985 to December 2012. The empirical results show that the sign of the correlation between the inflation rate and the unemployment rate is negative during recession periods but positive during boom periods.